Evaluation Of Transport Fare At Ferry Port On Track Waai - Umeputih In Maluku Province - Chairul Insani Ilham; Ong Argo Victoria; Anisa Tiara (IWJ : Inland Waterways Journal, 2021)
Waai Ferry Port is a port located in Waai Village, Central Maluku Regency which serves the Waai - Umeputih crossing. In terms of need, greatly affect the level of transportation services, especially in fulfilling public services. However, the prevailing fare are on the Waai route. Umeputih is now the when the track is still a pioneer route, not the that was applied when it became a commercial route. In addition, there is also a change in the Production Unit (SUP) in the type of vehicle class in accordance with Attachment I, Regulation of the Minister of Transportation Number 66 of 2019 concerning the Determination Mechanism and the Calculation Formulation of Ferries Transportation. The aims of this research are as follows: 1) To know the definition and unit system of ferries transportation. 2) Knowing the Fare on the Waai - Umeputih Line in Maluku Province in 2020. 3) Knowing the Fare on the Waai - Umeputih Line in Maluku Province in 2020. The research methodology used is direct field research, interview, literature / documentation and institutional. Then to analyze this based on Regulation of the Minister of Transportation Number 66 of 2019 concerning the Determination Mechanism and the Calculation Formulation of Ferries Transportation. The analysis used is load factor analysis, ship operational cost analysis, unit analysis and revenue analysis. The results of this study are 1) The Unit of Ferries Transportation which consists of the Passenger Transport and the for Vehicle and Their Cargo at the Ferry Port Based on the Applicable Regulations. 2) On the Waai - Umeputih Line in Maluku Province in 2020 is Irrelevant to Current Conditions, Due to Changes in Track Status and Changes in Production Unit (SUP) Units in the Management / Management System at PT. ASDP Indonesia Ferry (Persero) Ambon Branch in 2020. 3) Evaluation of Ferries Transportation on the Waai - Umeputih Route in Maluku Province Changes according to the following provisions: a) If there is an increase in the unit at the new, the regional government of the Regent of Central Maluku can do The Highest Reduction With Differentiation of 20% (Twenty Percent) From The Determined. b)The increasing of a fare nowadays is following Regulation of the Minister of Transportation Number 66 of 2019 concerning the Determination Mechanism and the Calculation Formulation of Ferries Transportation that stated a fare of production nowadays has increasing previous fare.